Sustainability of family livestock in the cerrado and pampa: analysis using the maderus methodology - Goñi, Liana Mendonça; Sturza, José Adolfo Iriam [UNESP]; da Silva, Nardel Luiz Soares (Centro Universitario de Maringa, 2024)
The social category of family cattle ranching represents a significant reality in family farming and an important ally to sustainability in the Brazilian rural sector. This study proposed to evaluate the main sustainability indices of family cattle ranching in the Cerrado and Pampa biomes. A total of 60 interviews were conducted in three municipalities belonging to the respective biomes, and IDRS scores of 7.23 and 7.32 were found for the Cerrado and Pampa, respectively. Under these conditions, it can be stated that family cattle ranching is an activity with the potential to contribute to the sustainability of the rural landscape of the municipalities of Pedra Preta, Quaraí, and Santana do Livramento, in terms of the environmental regulations of each territory and, to some extent, the production and reproduction of families, in a context of category representation for Mato Grosso and Rio Grande do Sul. The research results revealed realities of difficulties, potentialities, differences, and similarities in the different biomes with respect to cattle ranching. Future studies are suggested using MADERUS in other different Brazilian rural social categories.
Sustentabilidade da pecuária familiar no cerrado e pampa: análise por meio da metodologia maderus
Keywords: Cattle breeding; Family farming; Indicators